PENGARUH CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR), NON PERFORMING LOAN (NPL) DAN NNET INTEREST MARGIN (NIM) TERHADAP RETURN ON ASSET (ROA) (STUDI PADA BANK UMUM DENGAN METODE KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016) - Faizah, Rahmawati Nur; Saryadi, Saryadi (Jurnal Ilmu Administrasi Bisnis, 2018)
Return On Assets (ROA) is a profitability ratio to measure the ability of banks in generating profits so that the greater the ratio of ROA, the better performance of the bank. ROA at conventional commercial banks listed on the IDX continues to decline from 2012 to 2016. The ratios that are expected to affect profitability are CAR, LDR, NPL and NIM. The purpose of this study was to determine the effect of CAR, LDR, NPL and NIM on ROA. This type of research is explanatory research. The population of this study is 43. The population of this study are 28 banks with criteria of conventional commercial banks listed on the BEI before 2012 and remain registered until the end of 2016. Analysis techniques used are correlation analysis, determination coefficient test, linear regression test, and significance test using SPSS 21 data processing application. Result and discussion: CAR and LDR have no significant effect on ROA. NPL had a significant negative effect on ROA of 39.2%. NIM positively significant positive to ROA of 32.9%. CAR, LDR, NPL, and NIM have a significant effect on ROA of 53.8% simultaneously. Conclusion and suggestion: Based on multiple regression test, NPL variables has the greatest influence to ROA so it is expected that banks more to supervise and monitor the provision of credit in order to avoid bad loans.